Phytochemical Effects of Aqueous Leaves Extract of Tree Species as a Seed Priming Agent on Growth and Yield Attributes of Chickpea Crop - Hussain, Ejaz; Saif U Din; Muhammad Waqas; Qaisrani, Muhammad Inam Ullah; Akbar, Babur Ali; Awan, Barira; Muhammad Rizwan; Momina Bukhari (Indus Journal of Bioscience Research, 2025)
A field trial was carried out to investigate the phytochemical effects of aqueous leaves extract of tree species as a seed priming agent on growth and yield attributes of chickpea (NIFA-2005) crop; grown at AZRC-Arid Zone Research Centre, Dera Ismail Khan, Pakistan during winter season. The study was laid in complete randomized block design with seven treatments including control (tap water), leaf extract of Moringa (Moringa oleifera), Thorn mimosa (Acacia nilotica), Rose wood (Dalbergia sissoo), Pongam (Pongamia piñata), Conocarpus (Conocarpus lancifolius) and River red gum (Eucalyptus camaldulensis) and replicated thrice. Results revealed that control plots, where hydro priming was practiced, had comparable fallouts in almost all studied parameters to other treatments used. However, moringa extract had significantly higher effect on growth rate (8.03 g m-2 day-1), net assimilation rate (2.30 g m-2 day-1), plant height, weight of nodules (3.60 g), and grain yield 1875 (kg ha-1). Thus, the practice of moringa leaves extract is recommended to get the maximum yield of chickpea crop.